TINDAKAN SOSIAL NGELEM PADA ANAK USIA SEKOLAH DASAR DI KOTA TANJUNGBALAI - Anita, Anita; Fauzi, Fauzi; MR, M. Husen; Alwi, Alwi; Novianti, Novianti (FISIP Universitas Malikussaleh, 2024)
This research examines the social actions of ngelem among elementary school-aged children in Pasar Baru Village, Tanjungbalai City. The main focus in this study is the motives that encourage elementary school children to commit acts of ngelem, the impact of ngelem on children's education at school and the role of parents in preventing ngelem. This research uses Max Weber's social action theory. This research uses a qualitative method with a descriptive approach which aims to understand and describe the phenomena experienced by the research subjects. The data collection techniques used were observation, interviews and document utilization. Data analysis was carried out through the stages of data reduction, data presentation and drawing conclusions. The results of the research show that the motives that encourage elementary school children to act ngelem are a high sense of curiosity, the influence of playmates, so that they are accepted into the play group and looking for fun. Meanwhile, the impact of slowing down on children's education at school is not focusing on receiving lessons, difficulty managing emotions, poor attendance levels, loss of enthusiasm for learning and missing classes. The role of parents in preventing laxity is to spend time with their children, organize their children's daily activity schedules and instill religious values in their children.